Tamarind Seed Based Activated Carbon Prepared Via Cufe Layered For Caffeine Removal From Aqueous Solution - Aziz, Mohamad Fazrul Ikmal (Universiti Sains Malaysia, 2022)
Caffeine is an emerging contaminant in wastewater. In this study, tamarind seed based activated carbon (TSAC) modified by CuFe layered via microwave heating under the flow of carbon dioxide gas was produced for adsorption of caffeine from aqueous solution. Characterization of TSAC was conducted in terms of surface morphology, elemental analysis and proximate analysis. Besides, isotherm study was also carried out at different impregnation ratio (IR). TSAC was synthesized from agrowaste of tamarind seed through microwave heating activation under the flow of CO2 gas. Resulted TSAC was also succeeded in caffeine removal with Langmuir monolayer adsorption capacity of 214.25 mg/g. Relatively high BET surface area obtained for TSAC was 498.53 m2/g and the pore diameter was 2.19 nm. Furthermore, adsorption of caffeine onto TSAC increased when IR of CuFe increased. In addition, the optimum IR value was found to be 1.50 with caffeine uptakes of 65.48 mg/g and percentage removal of 69.84%. Moreover, isotherm study also revealed that adsorption of caffein onto TSAC followed Freundlich model. This signifies multilayer coverage and the dominance of physisorption.